Do Oral Steroids Aid Recovery in Children With Bell's Palsy?. (October 2014) - Ismail, Abdul Qader; Alake, Oluwaseyi; Kallappa, Chetana
There is growing evidence that steroids are not beneficial for treatment of paediatric patients with Bell's palsy. To investigate, we conducted a retrospective longitudinal study examining notes of 100 children, over 12 years coded for facial nerve palsy. Of the 79 diagnosed with Bell's palsy, all recovered, and for 46 patients we had data on interval from onset of symptoms to resolution (median duration in treated group = 5 weeks, range = 39; median duration in untreated group = 6 weeks, range = 11; P = .86). From our results, we conclude that all children with Bell's palsy recovered, with or without steroid treatment, with no statistically significant difference in symptoms duration. Complications of unresolved Bell's palsy can have important long-term functional and psychosocial consequences. Therefore, we need further research on use of steroids in children with complete/severe cases; it would be a shame to omit treatment due to "absence of evidence" rather than "evidence of absence."